Cambridge primary mathematics teacher$1 (Bs resource /s - Moseley, Cherri; Rees, Janet (New York : Cambridge University Press, 2014)
The Cambridge Primary Mathematics Teacher$1 (Bs Resource is designed to support teachers using the Cambridge Primary Mathematics curriculum. It offers practical guidance, teaching strategies, lesson plans, and assessment ideas to help educators deliver engaging, concept-based mathematics lessons. The resource aligns with Cambridge standards and emphasizes problem-solving, reasoning, and application of mathematical concepts in real-life contexts. It also includes differentiation tips for mixed-ability classrooms and links to learner$1 (Bs books and activity books.s
Keywords: Mathematics -- Cambridge Curriculum -- Teacher Resource -- Primary Education